2011
DOI: 10.1097/aln.0b013e31823497dd
|View full text |Cite
|
Sign up to set email alerts
|

First-line Therapy with Coagulation Factor Concentrates Combined with Point-of-Care Coagulation Testing Is Associated with Decreased Allogeneic Blood Transfusion in Cardiovascular Surgery

Abstract: First-line administration of coagulation factor concentrates combined with point-of-care testing was associated with decreased incidence of blood transfusion and thrombotic/thromboembolic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
289
1
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 399 publications
(316 citation statements)
references
References 63 publications
11
289
1
15
Order By: Relevance
“…The main confounding factors for bleeding include coagulation abnormalities depending on the type of preexisting liver disease and hyperfibrinolysis, particularly after reperfusion [6,7]. Advances in the understanding of the pathophysiology of coagulation and in the improvement of surgical skills, the introduction of specific techniques as well as point-of-care diagnostics and specific treatments have resulted in the significant reduction of blood loss [8,9]. However, in some patients with end-stage liver disease (ESLD) the risk to develop thrombosis is higher than to develop bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…The main confounding factors for bleeding include coagulation abnormalities depending on the type of preexisting liver disease and hyperfibrinolysis, particularly after reperfusion [6,7]. Advances in the understanding of the pathophysiology of coagulation and in the improvement of surgical skills, the introduction of specific techniques as well as point-of-care diagnostics and specific treatments have resulted in the significant reduction of blood loss [8,9]. However, in some patients with end-stage liver disease (ESLD) the risk to develop thrombosis is higher than to develop bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis of 3865 patients undergoing cardiovascular surgery demonstrated that the incidence of thromboembolic events is reduced through POC-based administration of coagulation factor concentrates [6]. The Guidelines of the Societies of Thoracic Surgeons and Cardiovascular Anesthesiologists have included the use of POC devices in their blood conservation guidelines to guide transfusion therapies [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thromboelastometry has already widely been used to monitor coagulation changes and to guide coagulation therapy in trauma patients [35,36,37,43,44,45,52,53,54], during liver transplantation [4,16,23,25,38,41,42,43,44,45,47,55,56], and during cardiac surgery [24,25,39,43,44,45,57,58,59,60,61]. …”
Section: Methodsmentioning
confidence: 99%